The Relationship between Sternberg’s Tridimensional Intelligence and Coping Strategies in Facing Trauma in Self-Care Women - Iravani, Leila; Iravani Abbariki, Khadijeh (International Journal of Education and Cognitive Sciences, 2022)
The present study was conducted with the aim of investigating the relationship between Sternberg's three-dimensional intelligence and coping strategies in facing trauma in self-care women. The descriptive research method was correlation type. The statistical population of the research was all female heads of households in Tehran in 2022. The research sample included 150 female heads of households in the 20th district of Tehran, who were supported by the Imam Khomeini Relief Committee. The sampling method was determined voluntarily. The research tools were Grigorenko and Sternberg's (2002) successful intelligence questionnaire and Andler and Parker's (1990) coping strategies questionnaire. The method of data analysis was Pearson's correlation coefficient and multivariate regression analysis using spss software. The research findings showed that there is a weak significant relationship between analytical intelligence, emotion-oriented strategies and avoidance strategies, but there is a strong positive significant relationship between creative and practical intelligence and problem-oriented, emotion-oriented and avoidance strategies. Also, the results of the research showed that the problem-oriented strategy has the ability to predict intelligence. It can be concluded that Sternberg's three-dimensional intelligence can play a positive role in coping strategies in facing trauma in self-care women.